2011
DOI: 10.5115/acb.2011.44.4.314
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional evaluation of an animal model for the retinal degeneration induced byN-methyl-N-nitrosourea

Abstract: The retinal degeneration (RD) is a general cause of blindness. To study its pathophysiology and evaluate the effects of new therapeutic agents before clinical trials, it is essential to establish reliable and stable animal models. This study evaluated a RD animal model in which blindness was induced by N-methyl-N-nitrosourea (MNU), a potent retinotoxin leading to apoptosis of photoreceptors. MNU was applied to the Sprague-Dawley rats by a single intraperitoneal injection in different doses (40, 50, and 60 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Our MEA results suggested that the onset and progression of MNU induced PR dysfunction were rapid and followed a time-depended manner. These findings are in agreement with the ERG examinations and previous histological reports (Jeong et al, 2011;Tsubura et al, 2010;Petrin et al, 2003). At the time point of P7, no obvious ERG waveform was detectable in the MNU treated eyes, while very small response could still be detected by these peripheral channels in the MEA recordings.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our MEA results suggested that the onset and progression of MNU induced PR dysfunction were rapid and followed a time-depended manner. These findings are in agreement with the ERG examinations and previous histological reports (Jeong et al, 2011;Tsubura et al, 2010;Petrin et al, 2003). At the time point of P7, no obvious ERG waveform was detectable in the MNU treated eyes, while very small response could still be detected by these peripheral channels in the MEA recordings.…”
Section: Discussionsupporting
confidence: 95%
“…Similar to human RP, MNU-induced retinopathy can also be diagnosed by the abnormities in the ERG waveforms (Petrin et al, 2003;Jeong et al, 2011). However, the ERGs represent the summated electrical physical activities of integral retinal neurons, and it would be difficult to distinguish the function of local retinal regions (Homma et al, 2009;Gao et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, apoptosis is the primary event in both human RP and MNUinduced RP models. 22,23 In our study, photoreceptor cell apoptosis was evident at 12 hours and peaked at 24 hours, followed by extensive photoreceptor cell loss 7 days later. Moreover, H&E staining showed that ONL thinning was more severe in the central than peripheral retina after MNU treatment, which differs from human RP.…”
Section: Discussionsupporting
confidence: 49%
“…MNU induces photoreceptor cell death in a variety of mammalian eyes with pathological aspects similar to those in patients with RP. Moreover, apoptosis is the primary event in both human RP and MNU‐induced RP models . Compared with other retinal degeneration models, MNU‐induced model has several advantages: (1) single intraperitoneal administration induces photoreceptor‐specific deterioration; (2) disease onset and progression are rapid, inducing remarkable damage usually within 7 days; and (3) the severity of the degeneration and the timing of disease onset can be easily controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been widely used in laboratory explorations for potential treatments. [9][10][11][12][13] Transcorneal electrical stimulation (TES) is a novel electrical approach to activate the retina, resulting in protective effects on subjective retinal neurons. 14 A series of animal experiments suggests that TES protects the retinal neurons from traumaticor genetic-induced degeneration, supporting its clinical utilization against various retinal and optical diseases, such as traumatic optic neuropathy, anterior ischemic optic neuropathy (AION), and retinal artery occlusions (RAOs).…”
mentioning
confidence: 99%